1995
DOI: 10.1073/pnas.92.11.4982
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ubiquitin-conjugating enzymes during terminal erythroid differentiation.

Abstract: A global cellular reorganization occurs during the reticulocyte stage of erythroid differentiation. This reorganization is accomplished partly through programmed protein degradation. The selection of proteins for degradation can be mediated by covalent attachment of ubiquitin. We have cloned cDNAs encoding two ubiquitin-conjugating (E2) enzymes, E2-20K and E2-230K, and found their genes to be strongly induced during the differentiation of erythroblasts into reticulocytes. Induction ofthe E2-20K and E2-230K gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 56 publications
1
60
0
Order By: Relevance
“…Our observation that UBE2H is strongly induced during erythrocyte differentiation of human CD34 ϩ primary cells is also in line with previous results (52). It was also demonstrated that UBE2H expression is up-regulated during differentiation of erythroblasts to reticulocytes and reduced during terminal differentiation stages (53,54). A similar expression pattern was described for Tal1, which is highly expressed in early erythrocyte stages and down-regulated during later stages of maturation (55,56).…”
Section: Discussionsupporting
confidence: 79%
“…Our observation that UBE2H is strongly induced during erythrocyte differentiation of human CD34 ϩ primary cells is also in line with previous results (52). It was also demonstrated that UBE2H expression is up-regulated during differentiation of erythroblasts to reticulocytes and reduced during terminal differentiation stages (53,54). A similar expression pattern was described for Tal1, which is highly expressed in early erythrocyte stages and down-regulated during later stages of maturation (55,56).…”
Section: Discussionsupporting
confidence: 79%
“…It is ubiquitously expressed, but preferentially in brain, skeletal muscle and heart tissues [21]. In erythroid cells, UBE2O is upregulated during the reticulocyte stage of erythroid differentiation [22,23]. The function of UBE2O remains mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin, a small chaperone protein, is common to all eukaryotic cells and plays an important role in proteasomal and lysosomal protein degradation. Ubiquitin is thought to facilitate proteolysis and organelle degradation during reticulocyte differentiation (Rapoport & Schewe 1986, Wefes et al 1995. There is an indication that ubiquitin acts in synergy with the 15-LOX pathway during mitochondrial membrane degradation in the reticulocytes (Dubiel & Rapoport 1989, van Leyen et al 1998.…”
Section: Introductionmentioning
confidence: 99%